Pharmacokinetic Interaction of Astragaloside IV with Atractylenolide I and Prim-O-Glucosylcimifugin in Male Sprague Dawley Rats - Song, Jue; Zheng, Shi-rui; Jin, Yong; Li, Jun (Planta Medica, 2014)
Astragaloside IV, atractylenolide I, and prim-O-glucosylcimifugin are main medicinal components of the traditional Chinese medicine prescription Yu-ping-feng which is composed of three herbs: Astragalus membranaceus, Atractylodes macrocephala, and Saposhnikovia divaricata. This study is aimed to assess the influence of atractylenolide I and prim-O-glucosylcimifugin on the pharmacokinetic profile of astragaloside IV so as to investigate the pharmacokinetic mechanisms of the Yu-ping-feng prescription. Fifteen Sprague Dawley rats were randomized to three groups; astragaloside IV, astragaloside IV plus atractylenolide I, and a combination of astragaloside IV, atractylenolide I, and prim-O-glucosylcimifugin were respectively administered to rats of these three groups via intragastric gavage. Serum samples were collected at different times after drug administration, and serum concentrations of astragaloside IV and atractylenolide I were simultaneously detected using HPLC-electrospray ionization-MS. Compared with administration of astragaloside IV alone, concentrations of astragaloside IV in the serum were significantly increased when it was given in combination with atractylenolide I or atractylenolide I+prim-O-glucosylcimifugin, with higher values for Cmax (p = 0.019 and p = 0.033 compared with astragaloside IV + atractylenolide I and astragaloside IV + atractylenolide I + prim-O-glucosylcimifugin groups, respectively) and AUC (p = 0.0052 and p = 0.0047 compared with astragaloside IV + atractylenolide I and astragaloside IV + atractylenolide I + prim-O-glucosylcimifugin groups, respectively). Improvement in mean oral Cmax and mean systemic serum exposure because of the pharmacokinetic interaction between astragaloside IV and atractylenolide I might explain the rationale for the use of multiple herbs in Yu-ping-feng and of combinations of A.membranaceus and A. macrocephala.
Keywords: pharmacokinetic interaction; astragaloside IV; atractylenolide I; Astragalus membranaceus; Atractylodes macrocephala; Yu-ping-feng; Leguminosae; Compositae; Umbelliferae